Cardiac rhabdomyoma as a possible new prenatal sonographic feature of Prader–Willi syndrome. Issue 1 (16th October 2021) - Traisrisilp, Kuntharee; Sirikunalai, Panarat; Sirilert, Sirinart; Chareonsirisuthigul, Takol; Tongsong, Theera
Abstract: We describe a unique case of a pregnancy with fetal Prader–Willi syndrome (PWS). A 40‐year‐old pregnant woman prenatally presented with polyhydramnios, decreased fetal movements, fetal growth restriction with normal Doppler study, and fetal cardiac rhabdomyoma, a possible new sonographic markers for PWS, at 31 weeks of gestation. The newborn had hypotonia and feeding difficulty. Molecular genetic study showed a normal copy number of the 15q11.2–q13.1 chromosomal region but hypermethylation pattern of this region, indicating PWS. Other than the combination of polyhydramnios, fetal growth restriction, and decreased fetal movements, cardiac rhabdomyoma was detected and possibly associated with PWS. In conclusion, PWS should be listed in differential diagnoses if fetuses having the following perinatal factors: polyhydramnios, decreased fetal movements, and growth restriction. Finally, cardiac rhabdomyoma, observed in this case, might possibly be associated with PWS, although further studies to confirm are needed.